2000
DOI: 10.1055/s-2000-9232
|View full text |Cite
|
Sign up to set email alerts
|

Die Achse I „Krankheitserleben und Behandlungsvoraussetzungen” der Operationalisierten Psychodynamischen Diagnostik (OPD) - Erfahrungen in der klinischen Praxis -

Abstract: In a selective survey, results on psychometric properties and aspects of application of the axis I, "illness experience and treatment preconditions" of the Operational Psychodynamic Diagnoses (OPD) are described. Following remarks on the role of defense and coping theories in the conceptualisation of the axis, its structure and contents are outlined. After a brief summary of findings on its interrater reliability, several aspects of validity are discussed. Results on discriminative validity show that axis I it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1
8

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 7 publications
1
2
1
8
Order By: Relevance
“…At the time of their OPD examination, patients who would later develop a panic disorder showed more severe impairment of self-experience, a greater burden of suffering, and less social support than did patients who remained psychologically healthy during the remainder of the study period. These findings corroborate, in part, data reported by Schneider et al [22] showing that patients with panic disorders exhibited levels of psychosocial integration that were lower than those seen in patients with other psychiatric disorders (i.e. first diagnoses of dysthymia, generalized anxiety disorder, depressive episodes, or personality disorders).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…At the time of their OPD examination, patients who would later develop a panic disorder showed more severe impairment of self-experience, a greater burden of suffering, and less social support than did patients who remained psychologically healthy during the remainder of the study period. These findings corroborate, in part, data reported by Schneider et al [22] showing that patients with panic disorders exhibited levels of psychosocial integration that were lower than those seen in patients with other psychiatric disorders (i.e. first diagnoses of dysthymia, generalized anxiety disorder, depressive episodes, or personality disorders).…”
Section: Discussionsupporting
confidence: 81%
“…first diagnoses of dysthymia, generalized anxiety disorder, depressive episodes, or personality disorders). Interestingly, patients with panic disorders in the study by Schneider et al [22] showed greater morbid gain than other patients, but also -in contrast to our findings -higher levels of social support.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Der FMP bildet die Einstellungen gegen ü ber somatischen und psychischen Beschwerden, wahrgenommene Ursachen dieser Beschwerden, Vorerfahrungen mit psychotherapeutischen Behandlungsformen und die Beurteilung der Eignung dieser Behandlungsformen f ü r die zuk ü nftige Therapie ab. Das Verfahren umfasst 47 Items (f ü nfstufi ge Antwortskala von 1 = " stimmt uneingeschr ä nkt " bis 5 = " stimmt ü berhaupt nicht " ), die zu 4 Merkmalsbereichen zusammengefasst werden: [20] . Hinsichtlich des Einfl usses des Alters der Patienten erweist sich die diagnostische Klassifi kation mittels der OPD Achse I ebenfalls als wirkungsvoll.…”
Section: Untersuchung ▼unclassified
“…Als hypothetisch relevante Patientenmerkmale wurden das Geschlecht, das Alter und die Zugeh ö rigkeit zu spezifi schen Krankheitsgruppen (ICD-10-Diagnose) gew ä hlt. Basierend auf klinischen und empirischen Befunden[19,20] wurde davon ausgegangen, dass weibliche Patienten psychosozialen Konzepten zur Ä tiologie psychischer und psychosomatischer St ö rungen aufgeschlossener gegen ü berstehen. Sie sollten dementsprechend psychotherapeutische Ma ß nahmen weniger skeptisch beurteilen und eine insgesamt h ö here Therapiemotivation aufweisen.…”
unclassified